New and interesting Portuguese Lepidoptera records from 2021 (Insecta: Lepidoptera) - Martin F. V. Corley; Helder Cardoso; João Nunes; Ana Valadares; Thijs Valkenburg (SHILAP, 2022)
13 species are added to the Portuguese Lepidoptera fauna, of which three are new for the Iberian Peninsula, and two species deleted, mainly as a result of fieldwork undertaken by the authors and others in 2021. In addition, second and third records for the country, new province records and new host-plant data for a number of species are included. A summary of recent papers affecting the Portuguese fauna is included.